2013
DOI: 10.1002/atr.1240
|View full text |Cite
|
Sign up to set email alerts
|

Analytic hierarchy process application in selecting the mode of transport for a logistics company

Abstract: #nofulltext#As a multi-criteria decision-making (MCDM) method, the analytic hierarchy process (AHP) has been used considerably to solve hierarchical or network-based decision problems in socio-economic fields. Following an in-depth explanation of the transport function in logistics and an overview of the MCDM methods, the AHP model is employed in the paper for a logistics company in selecting the most suitable way of transportation between two given locations in Turkey. The criteria used in the selection of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 69 publications
0
19
0
1
Order By: Relevance
“…The application of MCDM results in the ranking of alternatives, from the most to the least favorable, thus allowing comparison of alternatives. Some common methods for MCDA in transport applications include the technique for order of preference by similarity to ideal solutions (TOPSIS) [19,20], analytic hierarchy process (AHP) [21][22][23], grey evaluation method (GE) [24,25], simple additive weighting (SAW) [26], and elimination and choice expressing reality ELECTRA [27]. In particular, MCDM methods are often used for formulating DSFs for optimal technological system selection [28][29][30][31][32][33][34][35][36].…”
Section: Methodsmentioning
confidence: 99%
“…The application of MCDM results in the ranking of alternatives, from the most to the least favorable, thus allowing comparison of alternatives. Some common methods for MCDA in transport applications include the technique for order of preference by similarity to ideal solutions (TOPSIS) [19,20], analytic hierarchy process (AHP) [21][22][23], grey evaluation method (GE) [24,25], simple additive weighting (SAW) [26], and elimination and choice expressing reality ELECTRA [27]. In particular, MCDM methods are often used for formulating DSFs for optimal technological system selection [28][29][30][31][32][33][34][35][36].…”
Section: Methodsmentioning
confidence: 99%
“…The simple additive weighting (SAW), also known as weighted sum model, is one of the most popular and simple multicriteria decision analysis technique for evaluating a set of alternatives in terms of a set of criteria. In a multiple criteria decision problem with alternatives and criteria, the performance score of each alternative can be derived using following equation: * = ∑ =1 (12) where (for = 1, 2, … , and = 1, 2, … , ) represents the normalized rating of alternative with respect to criterion and represents the normalized weight of criterion . The alternative with maximum performance score ( * ) is considered as best alternative.…”
Section: Simple Additive Weighting (Saw)mentioning
confidence: 99%
“…This phase begins with forming a team of 5 experts responsible for identifying a set of selection criteria important to determine best mode of transportation. A list of selection criteria was prepared based on expert's opinion and literature survey ( [20], [15], [12], [4], [16], [8], [7]) and a calibration process was applied to narrow down the list to include only those criteria the travelers' feel pertinent to select a transportation mode. This process resulted in a set of eight criteria -1 : safety, 2 : speed, 3 : travel cost, 4 : interchange, 5 : accessibility, 6 : comfort, 7 : environment friendliness, and 8 : capacity.…”
Section: Application Of Proposed Model In Transportation Mode Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the perspectives of logistics safety, greenness, and social benefits, Binder et al [18] identified the factors affecting RLP's operational benefits, constructed a reasonable evaluation index system (EIS), and provided the intelligent park management center with the top and bottom design techniques for operation management platform. Kumru and Kumru [19] planned and designed the technical and functional architectures for intelligent RLP inventory management, which involves the goods dispatching command center, goods sales and distribution center, comprehensive management center, and logistics information interaction center. Sharp et al [20] provided new ideas for RLP intermodal transport and inventory management, with the aid of space-time positioning through crowd sensing, image recognition by multiple visual sensors, and adaptive selfoptimization by artificial intelligence (AI).…”
Section: Introductionmentioning
confidence: 99%